An Exploration of Characteristics and Behavioral Traits of DAISY Honorees and Nominees: A Qualitative Study. (January 2021) - Nair, Julie McCulloh; Merring, Paige; Jones, Bradley; Guney, Senem
Abstract : BACKGROUND: In the literature, an abundance of stories exist describing patient situations and caregiver actions, but only 2 studies were identified that outline DAISY honorees' actions and behavioral characteristics. OBJECTIVE: This study utilized patient nomination data and DAISY honoree insight to identify and gain better understanding of the characteristics and behavioral traits of DAISY nurses. METHODS: A grounded theory approach and purposive sample were used in this study, which was conducted in 2 phases using 2 different data sets. In phase 1, the NarrativeDx AI platform generated insights from DAISY nomination comments. In phase 2, a survey was administered to DAISY honorees collecting descriptive data that were analyzed in SPSS, whereas insights on DAISY nurses were collected via open-ended responses and analyzed using NVivo software. RESULTS: Three themes emerged in phase 1 from DAISY nomination data: caring, knowledge/skills, and reliability. A total of 37 DAISY honorees participated in phase 2. Most participants were bachelor's degree–prepared and worked day shift in the emergency department, critical care units, or medical-surgical units; some entered leadership roles post award, and 34% cited nursing as a 2nd career. Four themes emerged from their open-ended responses: engaging in care, environment of care, dedicated to care, and competence of care. Subthemes emerged in both analyses. CONCLUSIONS: The essence of caring was noted continuously in both nomination and honoree data. Further research aimed at discovering the characteristics and behaviors of DAISY honorees is recommended as examination of these factors may provide a deeper understanding of this exemplary group of nurses. Insights could be incorporated into training and practice programs aimed at increasing patient and nursing satisfaction. Abstract : Supplemental digital content is available in the text.